OXA-204 Carbapenemase in Clinical Isolate of Pseudomonas guariconensis, Tunisia - Nadia Jaidane; Wejdene Mansour; Lamia Tilouche; Pierre Châtre; Pauline François; Agnese Lupo; Saoussen Oueslati; Aymeric Jacquemin; Ali Lazzem; Sonia Karaborni; Laetitia Du Fraysseix; Yomna Ben Lamine; et al. (Emerging Infectious Diseases)
We report an OXA-204–producing Pseudomonas guariconensis clinical isolate in Tunisia, proving the spread of OXA-48 variants beyond Enterobacterales. The blaOXA-204 gene was carried on a 119-kb chromosomally integrated plasmid fragment, along with multiple additional resistance genes. Surveillance, diagnostic tools, and antimicrobial drug access are needed to mitigate spread of carbapenem-resistant pathogens.